Tracking the sterol biosynthesis pathway of the diatom Phaeodactylum tricornutum. Issue 3 (3rd July 2014) - Fabris, Michele; Matthijs, Michiel; Carbonelle, Sophie; Moses, Tessa; Pollier, Jacob; Dasseville, Renaat; Baart, Gino J. E.; Vyverman, Wim; Goossens, Alain
Summary: Diatoms are unicellular photosynthetic microalgae that play a major role in global primary production and aquatic biogeochemical cycling. Endosymbiotic events and recurrent gene transfers uniquely shaped the genome of diatoms, which contains features from several domains of life. The biosynthesis pathways of sterols, essential compounds in all eukaryotic cells, and many of the enzymes involved are evolutionarily conserved in eukaryotes. Although well characterized in most eukaryotes, the pathway leading to sterol biosynthesis in diatoms has remained hitherto unidentified. Through the DiatomCyc database we reconstructed the mevalonate and sterol biosynthetic pathways of the model diatom Phaeodactylum tricornutum in silico . We experimentally verified the predicted pathways using enzyme inhibitor, gene silencing and heterologous gene expression approaches. Our analysis revealed a peculiar, chimeric organization of the diatom sterol biosynthesis pathway, which possesses features of both plant and fungal pathways. Strikingly, it lacks a conventional squalene epoxidase and utilizes an extended oxidosqualene cyclase and a multifunctional isopentenyl diphosphate isomerase/squalene synthase enzyme. The reconstruction of the P. tricornutum sterol pathway underscores the metabolic plasticity of diatoms and offers important insights for the engineering of diatoms for sustainable production of biofuels and high‐value chemicals.